Dimensions of Social Exclusion : Ethnographic Explorations. - Ziyauddin, K. M. (Cambridge Scholars Publishing, 2009)
Dimensions of Social Exclusion focuses largely on social exclusion in the context of communities and social groups who have or have not been considered in discussing the benefits of mainstream inclusive society or development. Contemporary understanding of social exclusion has revived great interest among academics, researchers and policy makers in understanding problems from the perspectives of social exclusion. The decision to adopt the perspective of social exclusion has not been universal ...